KONSTRUKSI DAN ANALISIS MODEL MATEMATIKA RADIKALISME - Ariyanto Ariyanto (J-Icon : Jurnal Komputer dan Informatika, 2019)
An increase in the number of cases related to radicalism in Indonesia is an early warning for the government and is very dangerous for the lives of Indonesian people including the Bima community. Therefore, an anticipated strategy is required to determine the best control of the radicalism. This study aims: (1) to determine the attitude of university student radicalism in the City of Bima, (2) build a mathematical model that is in line with the problem of radicalism in the City of Bima, and (3) to construct the reproduction number from the mathematical model of radicalism, and use the to explain the dynamics of the spread of radicalism in the city of Bima. The following results have been obtained: (1) STKIP Bima students' perceptions of radicalism are categorized into three groups, namely the healthy group of 295 people (12%), the neutral group of 1,768 people (72%), and the radicalism (in perception) group of 393 people ( 16%), (2) The mathematical model has been validated against the real data obtained from the STKIP Bima student population in 2019. It shows that if the chance of moving individuals from neutral groups to radical groups is greater or equal with the opportunity of individuals from neutral groups to healthy groups, one person who believes in radicalism can produce four to five new individuals who understand radicalism.